Mesoarchean partial melting of mafic crust and tonalite production during high-T–low-P stagnant tectonism, Akia Terrane, West Greenland - Yakymchuk, C.; Kirkland, C. L.; Hollis, J. A.; Kendrick, J.; Gardiner, N. J.; Szilas, K. (Precambrian Research, 2020)
The Ministry of Mineral Resources and Labour, Greenland Government supported field and analytical work. NJG acknowledges support from Australian Research Council grant FL160100168. Different geodynamic models exist for the growth and differentiation of Archean continental crust, ranging from horizontal tectonics with subduction zones to vertical tectonics with foundering of greenstone sequences. U–Pb zircon geochronology, field relationships, and pressure–temperature constraints from granulite-facies metabasite of the Akia Terrane of the North Atlantic Craton in West Greenland show that this terrane grew through two major magmatic growth episodes: an earlier one at c. 3.2 Ga, and a later one at c. 3.05–2.97 Ga. Phase equilibrium modelling for assemblages related to the latter indicates temperatures of >800 °C at <0.9 GPa, consistent with a high apparent geothermal gradient and implies thin crust. Granulite-facies metamorphism and partial melting occurred in the absence of pervasive ductile deformation as indicated by nebulitic, undeformed pyroxene-bearing leucosome in metabasite gneiss. Trace element modelling suggests that c. 3.0 Ga tonalite at the current exposure level in the Akia Terrane was generated at pressures of >0.8 GPa in the stability field of garnet. U–Pb zircon geochronology and existing Hf isotope data are also consistent with a model involving protracted Mesoarchean magmatic growth with limited mantle addition during a prolonged period of high temperatures in a relatively stagnant tectonic regime prior to Neoarchean compressional tectonism in the Akia Terrane. Peer reviewed